Pendidikan Perkoperasian "Dasar Perkoperasian, Kelembagaan Koperasi dan Usaha Koperasi" Bagi Calon Anggota di SMK Koperasi, Daerah Istimewa Yogyakarta - Kalifatullah Ermaya, Sir (E-Coops-Day, 2024)
The number of cooperatives in Indonesia continues to increase rapidly, but there are still many cooperative members and employees who do not understand the principles of cooperatives, so many cooperatives are not active. One of the cooperatives in Daerah Istimewa Yogyakarta is the Employee Cooperative at SMK Cooperative, Yogyakarta. The Community Service Team provides guidance in the form of material regarding the basics of cooperatives, cooperative institutions, and cooperative businesses so that prospective members can participate better and employees work more actively to improve their performance. Some of the cooperative theories provided in this Community Service activity are basic cooperatives, definition of cooperatives, foundation, principles and objectives for establishing cooperatives, cooperative principles, characteristics of cooperatives, types of cooperatives, and business activities in cooperatives. In practice, there needs to be a strengthening of prospective members so that they have strong motivation to cooperate. It is hoped that educational development for employees and prospective members will be able to contribute to all levels of management, employees, and members.